The Relationship Between Individual Social Capital and Life Satisfaction Among University Students in China: The Mediating Role of Resiliency - Zhang, Xiaomei; Ju, Soon-Yew (International Journal of Social Science Research, 2024)
This present paper has aimed to investigate the university students’ life satisfaction in the city of Ji’nan in China. Due to the important role of university students, their life satisfaction has been valuable and necessary to be examined. The extent literature about students’ life satisfaction has left a blank for the three variables in the study. Therefore, this paper has tried to give an explanation for the relationship among university students’ life satisfaction and individual social capital by the mediating effect of resilience, which may be a new conceptual model seldom conducted in previous studies, especially in Ji’nan. As a non-experimental descriptive research design, a quantitative (deductive reasoning) technique has been employed to quantify the issue, in which survey questionnaire has been used to gather numerical data and then turned into practical statistics.